Avaliação comportamental do processamento auditivo em adultos antes e após a reabilitação auditiva - Cristiane Bueno Sales (2013)
Introduction: Hearing is fundamental to human communication. The impact of hearing loss can cause biological, psychological and social consequences. The auditory process of rehabilitation aids individuals with hearing loss to improve communication performance present in daily life situations. There are good reasons to believe in physiological changes of the central auditory system due to its stimulation after auditory adaptation associated with hearing training. Objectives: To describe the findings of behavioral tests of auditory processing in patients with mild to moderate neurosensory hearing loss and to verify if the auditory rehabilitation produces changes in the response patterns to these tests. Methods: This is an experimental study in which the findings of behavioral assessment of auditory processing of 22 patients with mild or moderate post-lingual hearing loss were compared before and after rehabilitation. We studied all the mechanisms involved in the behavioral assessment of auditory processing of the four major functional categories proposed in the literature. Results: Auditory rehabilitation in patients with mild to moderate hearing loss caused significant improvement of auditory processing. Unlike previously published studies, the comparison of the results of the initial and final evaluations did not suffer influence of other variables. These results suggest that the response patterns of the adult central auditory system may change with auditory rehabilitation. Conclusion: The results emphasize the importance of routine indication by Health Care Hearing Services of behavioral assessments of auditory processing and auditory rehabilitation, including the hearing aid fitting and the training of listening skills, regardless of patient age. The hearing aid fitting associated with improvement in the speed of auditory processing may contribute to better prepare patients to daily life situations, resulting in more adequate social integration.